Neuroinvasive Seronegative West Nile Virus in the Setting of R-CHOP Chemotherapy for Diffuse Large B-Cell Lymphoma. Issue 6 (November 2018) - Yuen, Alexander D.; Liu, Jason Y.; Betancourt, Jaime
Abstract : Abstract: West Nile virus (WNV) is a mosquito-borne infectious disease that can produce potentially life-threatening meningoencephalitis in immunocompromised individuals. In 2017, there were 536 human cases of WNV in California, with 43 fatalities reported to the California Department of Public Health. Peak mosquito transmission periods are in the late summer and early fall when mosquitoes are maximally viremic. In addition to risk factors such as advanced age, malignancy, or prior organ transplantation, the probability of progression to severe, neuroinvasive disease has been reported to be significantly higher in individuals suffering from lymphoma receiving rituximab in addition to other oncologic treatments. Here, we describe the case of a patient who recently received chemotherapy with rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine, and prednisone for diffuse large B-cell lymphoma, complicated by meningoencephalitis due to seronegative neuroinvasive WNV infection, ultimately resulting in death. Abstract : West Nile virus is an arbovirus that can cause potentially fatal meningoencephalitis. Peak transmission periods in California occur in August and September. Limited therapeutic options are available for treatment outside of supportive care, especially in the setting of immunosuppression.